Morphometric Analysis of Sand Dunes and the Speed of Their Displacement in Sistan Plain - Mahdi Heydari Nasab; Amir Karam; Hosein Negaresh; Ahmad Pahlavanravi (کاوش‌های جغرافیایی مناطق بیابانی, 2019)
The characteristics of Sistan plain, such as river sedimentation, blowing of erosive winds, especially 120-day winds, and the droughts in the past 20 years have made a suitable situation for wind erosion. One of the concrete symbols of wind erosion is sand displacement. Since the regions of sand displacement in this study were residential, the aim of this study was set to conduct a morphometric analysis of sand dunes, their displacement speed, and their role in posing hazards to these areas. To analyze the role of morphometric parameters in the displacement of barkhans, out of 10 barkhans formed in two wind erosion centers, seven were selected. Then, during the 120-day wind period in Sistan area, their displacement was detected and documented. Afterwards, using the SPSS software, the regression analyses were done on the length, width, height, area, and the displacement of the ​​barkhans. The results indicated a negative correlation between the length of the barkhans and their displacement, while there was no significant correlation between the other parameters and the displacement.